He's Homotopy Perturbation Method for Solving Korteweg-de Vries Burgers Equation with Initial Condition - İnç, Mustafa (Wiley, 2010)
In this article, we present the Homotopy Perturbation Method (Shortly HPM) for obtaining the numerical solutions of the Korteweg-de Vries Burgers (KdVB) equation. The series solutions are developed and the reccurance relations are given explicity. The initial approximation can be freely chosen with possibly unknown constants which can be determined by imposing the boundary and initial conditions. The results reveal that HPM is very simple and effective. (C) 2009 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq 26: 1224-1235, 2010
Keywords: homotopy perturbation Method; Korteweg-de Vries Burgers equation; solitary wave solution